Sexual violence and risk factors among night shift female college students in Hawassa city, South Ethiopia, 2020 - Hawi Leul Esayas; Hirut Gemeda; Teshome Melese; Gebremariam Temesgen Birgoda; Bezabih Terefe; Samuel Abebe; Muluken Bekele; Fitsum Wolde; Bamlaku Birie (BMC, 2023)
Abstract Background Sexual violence is any sexual act, attempt to obtain a sexual act, unwanted sexual comments or advances, against a person's sexuality using coercion, by any person regardless of their relationship to the victim, in any setting. Several studies were undertaken on sexual violence among students in general. Nevertheless, there is paucity of information about sexual violence among night shift students in particular; even if they are more vulnerable to sexual violence due to the nature of the class time. The government has embraced legal and policy frameworks to discourse the problem of sexual violence in Ethiopia; nevertheless, the problem still is quite pervasive. Objective This study was aimed to assess the prevalence of sexual violence and risk factors among night shift female college students in Hawassa city. Methods Institution-based cross-sectional study design was employed. A structured questionnaire was used to collect the data from 345 study participants. Systematic random sampling technique was used to choice study participants. Epi data version 3.1statistical software and Statistical Package for Social Sciences version 22.0 were used to enter and analysis the data. Both bivariable and multivariable logistic regression analyses were performed to recognize risk factors. P values < 0.05 with 95% confidence level were used to state statistical significance. Results A total of 330 students were participated in the study making a response rate of 95.6% with a mean age of 24.9. The prevalence of last 12 month sexual violence was 202 (61.2%) 95% CI (55.8, 66.4) which includes rape, attempted rape and sexual harassment. The 12 month prevalence of each form of violence was 46 (13.9%) 95% CI (10.6, 17.9), 23 (6.9%) 95% CI (3.6, 10.9) and 163 (49.4%) 95% CI (46.2, 53.6) of rape, attempted rape and sexual harassment respectively. The independent predictors of sexual violence having a father with no formal education (AOR = 2.39, 95% CI 1.04, 5.33) presence of multiple sexual partners (AOR = 3.44, 95% CI 1.64, 7.2), having sexual partner (AOR = 1.89, 95% CI 1.03, 3.5), and consuming alcohol (3.55, 95% CI 1.84-6.85) by the victims. Conclusion This study shown that the prevalence of sexual violence is high among night shift female college students in Hawassa city. Having a father with no formal education, drinking alcohol, having multiple sexual partners and having sexual partner were more likely to have sexual violence within the last 12 month. Thus, students should prevent themselves from health risky behaviors and Hawassa educational bureau should be work on awareness creation concerning women empowerment with in marriage and Further broad and longitudinal studies are needed to determine the predictors of the problem among female students at Hawassa and Ethiopia as a whole.